Modeling the Transition to Cleaner Fuels Within the Maritime Industry - Nisiforou, Olympia; Deranian, Christopher; Alamanos, Angelos; Andres Garcia, Jorge; Koundouri, Phoebe (My University, 2025)
Shipping is a prominent sector within the Greek economy and faces several challenges in decarbonizing as prescribed by the FuelEU Maritime Regulation which is cornerstone of the EU’s decarbonization efforts in the shipping sector, specifically targeting the fuels used by vessels, implemented from 1 January 2025. FuelEU Maritime aims to reduce greenhouse gas intensity in ships above 5,000 gross tonnage at European ports by aiming for a 2% decrease by 2025 and an 80% reduction by 2050. The targets cover CO2, methane, and nitrous oxide emissions over the full lifecycle of fuels used onboard. From January 1, 2030, passenger and container ships must use on-shore power supply (OPS) or alternative zero-emission technologies in ports covered under Article 9 of the Alternative Fuels Infrastructure Regulation (AFIR). Member States may apply the obligation to ports not covered by Article 9 from January 1, 2030. FuelEU Maritime's goal-based and technology-neutral approach allows for innovation and the development of new sustainable fuels and energy conversion technologies. The regulation also provides flexibility mechanisms, supporting existing fleets in compliance strategies and rewarding first-movers for early investment in energy transition (Directorate of Mobility & Transport, 2024). In this paper we present the application of a free, opensource Investment Decision Support Tool, called MaritimeGCH, to model the transition to cleaner fuels within the maritime industry. The study tests a set of scenarios from slow to fast transition to cleaner fuels within the Greek shipping sector, and explores their effect on fleet optimization decisions. This set of scenarios reflects the potential evolution of some fuels starting phasing out (e.g. Oil and RefPO), being replaced by the transition fuels (LNG and LPG), while others (green fuels) will ultimately become more prevalent in the future (MeOH, NH3 and H2).